The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4238/gmr.15038449
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in growth hormone and leptin candidate genes with live weight traits of Brahman cattle

Abstract: ABSTRACT. Polymorphisms in candidate genes can produce significant and favorable changes in the phenotype, and therefore are useful for the identification of the best combination of favorable variants for marker-assisted selection. In the present study, an assessment to evaluate the effect of 11 single nucleotide polymorphisms (SNPs) in candidate genes on live weight traits of registered Brahman cattle was performed. Data from purebred bulls were used in this assessment. The dataset included birth (BW), weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(37 reference statements)
0
5
0
2
Order By: Relevance
“…Certain genotypic tendencies are better than others also not seen, although IGFBP-3 is one of the genes responsible for growth, it has a unique mechanism of work that is not yet fully known (Allard and Duan, 2018). IGFBP-3 has indirectly effect on cattle growth, unlike, for example, the Growth Hormone gene, which directly influences the cattle growth (Hernández et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Certain genotypic tendencies are better than others also not seen, although IGFBP-3 is one of the genes responsible for growth, it has a unique mechanism of work that is not yet fully known (Allard and Duan, 2018). IGFBP-3 has indirectly effect on cattle growth, unlike, for example, the Growth Hormone gene, which directly influences the cattle growth (Hernández et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…One of the genes that affect animal weight is the Leptin / LEP gene (Hernandez et al, 2016). Leptin is a hormone that is produced in white adipose tissue and secreted into the bloodstream as a 16 KD protein.…”
Section: Introductionmentioning
confidence: 99%
“…One of these genes, which is potentially polymorphic with a lot of selection benefit is the growth hormone gene [3]. Several studies have indicated the association between polymorphism of the bovine growth hormone (GH) gene and production traits although with divergent results in some cases [4][5][6]. Growth hormone is a polypeptide hormone secreted by somatroph cells from the anterior pituitary glands [7].…”
Section: Introductionmentioning
confidence: 99%